Development of an Environment-Based Assessment Instrument for Scientific Creativity in Science Classes at Junior High Schools - Syinta Nur; Iwan Wicaksono; Fadiatul Hasinah Muhammad (Jurnal Ilmiah Pendidikan Fisika, 2026)
Assessment in science education does not focus solely on cognitive aspects but must also measure students’ scientific creativity as it relates to environmental contexts. The purpose of this study is to determine the content validity, item validity, reliability, discriminative power, and difficulty level of the assessment instrument developed. This assessment instrument development study utilized the Borg and Gall development model. This model consists of ten stages; however, this research only applied eight stages, namely identifying potential problems, collecting information, product design, product validation, product revision, small group testing, and field testing. The subjects of this study were 105 seventh-grade students from classes A, B, and C at Junior High School. The results of the validation of the developed product by three expert validators showed an average score of 73.2%, categorized as valid; the item validation test showed a calculated r value > the table r value, thus confirming validity. The reliability of the items was 0.78, categorized as reliable. Analysis of the items’ discriminative power showed that 28.57% of the items were in the excellent category, 42.86% were in the good category, and 28.57% were in the fair category. The distribution of item difficulty levels was 42.86% easy, 28.57% moderate, and 28.57 % difficult. The result of the study shows that the assessment instrument developed has good characteristics and is suitable for measuring scientific creativity in science education.